Potential for Simultaneous Measurement of Magnetic Field and Temperature Utilizing Fiber Taper Modal Interferometer and Magnetic Fluid - Jie Li; Pengcheng Fan; Zhuang Tian; Li-Peng Sun; Bai-Ou Guan (IEEE Photonics Journal)
A single taper-based fiber modal interferometer with magnetic fluid integrated, which can have responses of dip wavelength and extinction ratio on the external magnetic field and temperature changes, is demonstrated. Within the magnetic field range from 50 to 100 Oe, the measured sensitivities are 88 pm/Oe and −0.1419 dB/Oe for dip wavelength and extinction ratio, respectively, and within the temperature range from 30 to 80 °C, the sensitivities are −282.67 pm/°C and −0.0528 dB/°C for dip wavelength and extinction ratio, respectively. A full analysis to the sensing mechanism is given and experimental results can verify the concepts of the device. The presented structure is featured with simplification, easy fabrication, and high sensitivity and should have potential applications in simultaneous magnetic field and temperature measurements.